1988
DOI: 10.1128/mcb.8.7.2713
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and metabolic regulation of the Drosophila melanogaster 3-hydroxy-3-methylglutaryl coenzyme A reductase.

Abstract: The enzyme 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase in Drosophila melanogaster synthesizes mevalonate for the production of nonsterol isoprenoids, which are essential for growth and differentiation. To (Mr, 98,165) that was similar to the hamster HMG CoA reductase. The C-terminal region had 56% identical residues and the N-terminal region had 7 potential transmembrane domains with 32 to 60% identical residues. In hamster HMG CoA reductase, the membrane regions were essential for posttransl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 47 publications
2
53
0
Order By: Relevance
“…The first section at the base of the leaf is the youngest, and the tip section is the oldest (Fig. 8) (Caelles et al, 1989;Learned and Fink, 1989), tomato (Narita and Gruissem, 1989), human (Luskey and Stevens, 1985), yeast (Basson et al, 1988), and Drosophila (Gertler et al, 1988). Relative to the wheat sequence, identical or conserved residues are shown in gray and residues that are neither identical nor conserved are shown in white.…”
Section: Developmental Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first section at the base of the leaf is the youngest, and the tip section is the oldest (Fig. 8) (Caelles et al, 1989;Learned and Fink, 1989), tomato (Narita and Gruissem, 1989), human (Luskey and Stevens, 1985), yeast (Basson et al, 1988), and Drosophila (Gertler et al, 1988). Relative to the wheat sequence, identical or conserved residues are shown in gray and residues that are neither identical nor conserved are shown in white.…”
Section: Developmental Gene Expressionmentioning
confidence: 99%
“…The degree of sequence homology among the three cDNAs is very high, as indicated by the shading. Figure 3 shows sequence homology comparison among HMGR genes by computer alignment of the translated wheat HMGR 18 partial cDNA sequence with that from Arabidopsis (Caelles et al, 1989;Learned and Fink, 1989), tomato (Narita and Gruissem, 1989;Narita et al, 1991), human (Luskey and Stevens, 1985), yeast (Basson et al, 1988), and Drosophila (Gertler et al, 1988).…”
Section: Isolation and Characterization Of Hmgr Cdna By Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is unlikely that this structural similarity in the transmembrane regions has been maintained only to provide sensitivity to sterol-mediated degradation. Since mevalonate affects the overall protein level, decreasing synthesis and increasing the rate of HMG-CoA reductase degradation [39,401, it has been suggested that conservation of these domains may be essential for recognizing specific mevalonate derivatives or their binding proteins [5]. Indeed, Simoni and coworkers showed that the and cholesterol-triggered degradation [42].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the primary structure of HMG-CoA reductase is known for a variety of eukaryotic organisms, including mammals [23- [5]. The comparison of B. germanica HMGCoA reductase with those of these species reveals extensive conservation, especially in the catalytic domain, which is located in the C-terminal region (44 -66 % identical amino acid residues).…”
Section: Comparison With Other Hmg-coa Reductase Sequencesmentioning
confidence: 99%